If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -2b + 3 = 4 Reorder the terms: 3 + 4a + -2b = 4 Solving 3 + 4a + -2b = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + 4a + -3 + -2b = 4 + -3 Reorder the terms: 3 + -3 + 4a + -2b = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 4a + -2b = 4 + -3 4a + -2b = 4 + -3 Combine like terms: 4 + -3 = 1 4a + -2b = 1 Add '2b' to each side of the equation. 4a + -2b + 2b = 1 + 2b Combine like terms: -2b + 2b = 0 4a + 0 = 1 + 2b 4a = 1 + 2b Divide each side by '4'. a = 0.25 + 0.5b Simplifying a = 0.25 + 0.5b
| 4+3(x+2)=10 | | 5x+x=26 | | 3x-12=x+4 | | 6x=35 | | 7-42x=1 | | 2x=-10y+90 | | 4x+28=6x-15 | | -4(a+3)-7= | | 114=-2x-8+5x | | 0=5-5y+7x | | 14x^2-46x+12=0 | | 4n+1=4n+1 | | 4x+6-7x+9=18 | | 6-(2n+3)-4n=6 | | 2x=5x-30 | | 12z-1=z^2+35 | | (x-9)+(.5x)=180 | | -3=3w-(4w+6) | | y^2+12y+20= | | 6=2(x+8)-5y | | 7x-8y=16 | | m^2+13m+40=0 | | 4x+5=11-3x | | -10x+3=5x-2 | | 3x-22= | | 2x-22= | | 3x-34= | | 3x^2-6x+2k=0 | | 3x=(x+1)(x+2)+8 | | 4(6+2x)=0 | | x+15=2(x-10) | | x+15=2(x-15) |